Seven hundred million to one: Personal action in reversing language shift - Dauenhauer, Richard (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2005)
AbstractThe paper considers what influence a single person can have on language survival and transmission of knowledge, comparing and contrasting the situation of large languages such as Putonghua (traditionally called Mandarin Chinese, with 700 million speakers) and small languages such as Eyak with as few speakers as one. It examines the delights and dilemmas of such work, the practical results (such as texts and documents) and the spiritual rewards (mostly satisfaction), drawing examples from our own work of the last 35 years with Tlingit, and from the work of colleagues, especially Michael Krauss, in the context of a volume celebrating his 70th birthday and 45 years of work on behalf of Alaska Native languages and endangered indigenous languages around the world, especially in the circumpolar north. The paper is by design an informal and non-technical address to the general reader, especially members of communities whose indigenous languages are endangered.